The Relationship Between Interpersonal Communication and Perception of Organizational Cohesion - Putri, Handyta Tiara; Davira S, Carelene; Putri, Najwa Nabila Rigusha; Junisah, Bunga Ayu; Tiatri, Sri (Manunggal Halim Jaya, 2026)
This study aims to determine the relationship between communication, interpersonal, and perception of Organizational cohesion among employees of private companies in Greater Jakarta (Jabodetabek). Interpersonal communication involves the direct exchange of messages involving aspects such as self-concept, self-expression, and openness. Organizational cohesion reflects the extent to which members feel socially connected and connected in carrying out group tasks. This study used a quantitative correlational approach with 100 respondents selected through purposive sampling. The instruments used were an interpersonal communication questionnaire based on Bienvenu's theory and organizational cohesion based on the GEQ by Carron et al. The results of the analysis showed no significant relationship between interpersonal communication and organizational cohesion (r = -0.084). This finding differs from previous research and is thought to be influenced by contextual factors such as organizational culture and the dominance of formal communication. Nevertheless, interpersonal communication remains important in creating a healthy and harmonious work environment.